Embedded cmc hypersurfaces on hyperbolic spaces (2011)
In this paper we will prove that for every integer $n and gt;1$, there exists a real number $H_0-2π$, then, $H$ can be realized as the mean curvature of an embedding of $H^{n-1}× S^1$ in the $(n+1)$-dimensional space $H^{n+1}$.